1999
DOI: 10.2169/internalmedicine.38.472
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Methylcobalamin Treatment for Uremic and Diabetic Neuropathy in Chronic Hemodialysis Patients.

Abstract: Object: To study the effects of the intravenous administration of methylcobalamin, an analogue of vitamin B12, for uremic or uremic-diabetic polyneuropathy in patients whoare receiving maintenance hemodialysis. An ultra-high dose of vitamin B12 has been reported to promote peripheral nerve regeneration in experimental neuropathy. Methods: Nine patients received a 500|ig methylcobalamin injection 3 times a week for 6 months. The effects were evaluated using neuropathic pain grading and a nerve conduction study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 11 publications
(10 reference statements)
1
38
0
1
Order By: Relevance
“…This effect has been attributed to the effect of vitamin B12 on axonal conduction (Wang et al, 2005). In the treatment of patients presenting with diabetic polyneuropathy, treatment with vitamin B12 led to a reduction in pain and paresthesia along with significant improvement of ulnar motor and median nerve conduction velocities (Kuwabara et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been attributed to the effect of vitamin B12 on axonal conduction (Wang et al, 2005). In the treatment of patients presenting with diabetic polyneuropathy, treatment with vitamin B12 led to a reduction in pain and paresthesia along with significant improvement of ulnar motor and median nerve conduction velocities (Kuwabara et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, "functional" deficiency of Cbl has recently been suggested in the pathogenesis of both Alzheimer disease and AIDS myelopathy. 43,44 Moreover, pharmacologic doses of methylcobalamin can improve measures of both cardiac autonomic dysfunction and peripheral neuropathy in diabetic subjects, [45][46][47] and high doses of methylcobalamin also accelerate nerve regeneration in rats with acrylamide neuropathy. 48 The observation that methylcobalamin can serve as a methyl donor in vitro in the DNA methylase reaction provides one possible mechanism for a pharmacologic effect of Cbl therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of high-dose intravenous administration of the vitamin B 12 analog methylcobalamin (500 µg 3 times per week) over a 6-month period was evaluated in chronic hemodialysis patients presenting diabetic neuropathy. The authors reported reduction in pain and paresthesia along with significant improvement of ulnar motor and median nerve conduction velocities [27]. Methylcobalamin was also shown to be effective in the treatment of diabetic neuropathy at oral doses of 500 mg; treatment resulted in improvement in pain as well as somatosensory and autonomic symptoms [28,29].…”
Section: Discussionmentioning
confidence: 99%